2006
DOI: 10.1007/s10508-006-8991-0
|View full text |Cite
|
Sign up to set email alerts
|

Power, Control, and Intimate Partner Sexual Violence in Haiti

Abstract: This study sought to determine how power and control in intimate relationships influenced women's exposure to sexual violence. Multilevel modeling was used to determine the risk of partner sexual violence in the past 12 months among 2240 women aged 15-49 years who were currently married or cohabiting. The data were drawn from the 2000 Haiti Demographic and Health Survey. Strong positive effects on intimate partner sexual violence were found for husband's jealousy and perpetration of controlling behavior and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
157
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(191 citation statements)
references
References 62 publications
28
157
1
5
Order By: Relevance
“…Their lives are further constrained by gender hierarchies that limit access to employment and education. This corroborates findings from research prior to Haiti’s earthquake that highlighted associations between women’s risk of IPV and not completing primary school, family contexts of IPV, and unequal relationship power[14,35], and post-earthquake research that situated women’s IPV risks in contexts of poverty and patriarchal gender norms [36]. This study contributes to the body of literature on internally displaced youths’ experiences post-disaster and in contexts of protracted crises by demonstrating the multi-level, intersectional nature of violence – as well as highlighting coping strategies that include hope, social support, and opportunity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Their lives are further constrained by gender hierarchies that limit access to employment and education. This corroborates findings from research prior to Haiti’s earthquake that highlighted associations between women’s risk of IPV and not completing primary school, family contexts of IPV, and unequal relationship power[14,35], and post-earthquake research that situated women’s IPV risks in contexts of poverty and patriarchal gender norms [36]. This study contributes to the body of literature on internally displaced youths’ experiences post-disaster and in contexts of protracted crises by demonstrating the multi-level, intersectional nature of violence – as well as highlighting coping strategies that include hope, social support, and opportunity.…”
Section: Discussionsupporting
confidence: 83%
“…Research conducted before Haiti’s 2010 earthquake highlighted that men’s perpetration of IPV was associated with men’s unemployment, neighborhood poverty, and men’s endorsement of traditional gender roles, including a man’s right to beat his wife [14,35]. We found young internally displaced women at the intersection of displacement and precarious housing, extreme poverty, and inequitable gender norms, are at elevated risk of survival sex work, IPV, and GBSV.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was in agreement with a study conducted in Haiti, which found that women in communities with a high proportion of female‐headed households showed increased risk of sexual IPV 23. Likewise, communities in the USA with large proportions of female‐headed households tend to have increased levels of violence against women 24.…”
Section: Discussionsupporting
confidence: 92%
“…Male sexual jealousy or "male sexual proprietariness" (Daly et al, 1982) is one of the most frequently cited causes of intimate partner violence, both physical and sexual (e.g., Buss, 2000;Daly & Wilson, 1988;Daly et al, 1982;Dobash & Dobash, 1979;Dutton, 1998;Dutton & Golant, 1995;Frieze, 1983;Gage & Hutchinson, 2006;Russell, 1982;Walker, 1979). Physical violence is a tactic used by men to restrict an intimate partner's behavior, especially her sexual behavior outside the intimate relationship (Buss & Malamuth, 1996;Daly & Wilson, 1988;Wilson & Daly, 1996) and is best understood as the behavioral output of male sexual jealousy (Buss, 1996(Buss, , 2000.…”
Section: Physical Violencementioning
confidence: 99%
“…Some researchers have hypothesized that sexual coercion in intimate relationships is motivated by men's attempts to dominate and control their partners (e.g., Basile, 2002;Bergen, 1996;Frieze, 1983;Gage & Hutchinson, 2006;Gelles, 1977;Meyer, Vivian, & O'Leary, 1998;Watts et al, 1998) and that this expression of power is the product of men's social roles (e.g., Brownmiller, 1975;Johnson, 1995;Yllo & Straus, 1990). Results relevant to this hypothesis are mixed.…”
Section: Sexual Violencementioning
confidence: 99%